Analysis of Intellectual Capital, Organizational Cultture, and Individual Diversity on Performence of Police Members at the East Java Regional Polices’s Narcotics - Putri, Nonny Saskia Ramadhani Mutiara; Sukarno, Gendut (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine the impact of intellectual capital, organizational culture, and individual diversity on the performance of members of the East Java Regional Police Directorate of Narcotics. This research employs a quantitative approach, utilizing questionnaires with a Likert scale ranging from 1 to 5 to assess responses. The sampling technique applied is proportional sampling, with a sample size of 65 respondents calculated using the Slovin formula. Data analysis was conducted using Structural Equation Modelling – Partial Least Squares (SEM-PLS). The findings indicate that intellectual capital, organizational culture, and individual diversity positively and significantly affect performance.